Evidence for monoclinic crystal structure and negative thermal expansion below magnetic transition temperature in Pb (Fe12 Nb12) O3 - Singh S.P.; Pandey D.; Yoon S.; Baik S.; Shin N. (My University, 2025)
The existing controversy about the room temperature structure of multiferroic Pb (Fe12 Nb12) O3 is settled using synchrotron powder x-ray diffraction data. Results of Rietveld refinements in the temperature range of 300-12 K reveal that the structure remains monoclinic in the Cm space group down to 12 K, but the lattice parameters show anomalies at the magnetic transition temperature (TN) due to spin-lattice coupling. The lattice volume exhibits negative thermal expansion behavior, with α=-4.64× 10-6 K-1, below TN. © 2007 American Institute of Physics.